2017
DOI: 10.1038/s41598-017-05007-7
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence via Reverse Intersystem Crossing from Higher Triplet States in a Bisanthracene Derivative

Abstract: To elucidate the high external quantum efficiency observed for organic light-emitting diodes using a bisanthracene derivative (BD1), non-radiative transition processes as well as radiative ones are discussed employing time-dependent density functional theory. It has been previously reported that the observed high external quantum efficiency of BD1 cannot be explained by the conventional thermally activated delayed fluorescence involving T1 exciton nor triplet-triplet annihilation. The calculated off-diagonal v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…[11][12][13][14] In addition to these exciting applications of TADF, the fundamental processes in TADF are also attracting considerable interest in both experimental and theoretical fields. [15][16][17][18][19][20][21][22][23][24][25][26] In this case, the goal is to achieve a sufficient understanding of these processes to realize a high RISC rate (k RISC ) by judicious designing and optimizing the most suitable chemical structures, emission environments, and so on. Increasing the k RISC suppresses triplet state quenching and is, therefore, beneficial for reducing roll-off in OLEDs and organic laser diodes.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] In addition to these exciting applications of TADF, the fundamental processes in TADF are also attracting considerable interest in both experimental and theoretical fields. [15][16][17][18][19][20][21][22][23][24][25][26] In this case, the goal is to achieve a sufficient understanding of these processes to realize a high RISC rate (k RISC ) by judicious designing and optimizing the most suitable chemical structures, emission environments, and so on. Increasing the k RISC suppresses triplet state quenching and is, therefore, beneficial for reducing roll-off in OLEDs and organic laser diodes.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative to TADF for efficient OLED emission makes use of higher triplet states and their reverse intersystem crossing (HIGHrISC). [12][13][14] HIGHrISC was shown to occur in aromatic carbonyls. [15] In these carbonyls, fast rISC starting from a higher triplet state of nπ* character may occur.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative to TADF for efficient OLED emission makes use of higher triplet states and their reverse intersystem crossing (HIGHrISC) [12–14] . HIGHrISC was shown to occur in aromatic carbonyls [15] .…”
Section: Introductionmentioning
confidence: 99%
“…Sato et al have already reported that, in fluorescent dopants employed in organic lightemitting diodes (OLEDs), radiative and non-radiative transitions from a triplet excited state T n (n > 1) to all the lower triplet excited states can be suppressed due to the pseudodegenerate electronic states. [18][19][20] The pseudo-degeneracy leads to cancellation of the overlap density between the excited states, which generates T n excitons with long lifetimes. This enables the fluorescence via higher triplets (FvHT) mechanism for OLEDs, that is fluorescence utilizing the reverse intersystem crossing (RISC) from T n to singlets.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 The FvHT mechanism is proposed to explain the mechanism of electroluminescence in some OLED dopants with large ∆E S 1 −T 1 , where T 1 excitons cannot overcome the energy difference thermally. 19,23 A cyano-substituted 1,2-bis(pyridylphenyl)ethene (CNPPE) ( Fig. 1) has been reported to exhibit the AIEE behavior in solid phase.…”
Section: Introductionmentioning
confidence: 99%